2020
DOI: 10.7150/jca.46066
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin uptake in ascitic lymphoma model: resistance or curability is governed by tumor cell density and prolonged drug retention

Abstract: Background/Aims: Chemotherapy resistance of malignancies is a universal phenomenon which unfavorably affects therapeutic results. Genetic adaptations as well as epigenetic factors can play an important role in the development of multidrug resistance. Cytotoxic drug content in plasma of cancer patients is known to variate up to one hundred-fold regardless of the same dose injected per m 2 body surface. The relationship between plasma concentrations, tissue uptake, and chemotherapy response is not completely und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Liposome size is known to affect the stability, uptake, and metabolism of liposome-based formulations [ 26 ]. We found that Lip and M-Lip were spherical nanoparticles with a similar size of ~100 nm ( Figure 1 A,C).…”
Section: Resultsmentioning
confidence: 99%
“…Liposome size is known to affect the stability, uptake, and metabolism of liposome-based formulations [ 26 ]. We found that Lip and M-Lip were spherical nanoparticles with a similar size of ~100 nm ( Figure 1 A,C).…”
Section: Resultsmentioning
confidence: 99%
“…The tumors were allowed to grow for 10 d (about 50 mm 3 in diameter) before any intervention was initiated. The mice were treated with Adr (5 mg/kg) [ 18 , 19 ] or Cyt (100 mg/kg) [ 20 , 21 ] by oral tube feeding on d 6 and 24. The mouse weight was recorded once every 6 d. After 30 d, the mice were euthanized by excessive injection of pentobarbital sodium at 100 mg/kg, and their tumors were harvested.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 Owing to the heterogeneity of solid tumors, lower doses of chemotherapeutic drugs reach the tumor site than the dose administered. 11 Zaleskis et al, reported that similar doses of chemotherapeutic drug (doxorubicin) administered in tumor bearing mice resulted in three different responses (cure, resistance, and relapse), 12 explaining the important role of heterogeneous cell populations. Chemotherapy drugs are also known to be present in the associated tissue for longer periods of time.…”
Section: Introductionmentioning
confidence: 99%